Physician visits for psoriasis and reduced risk of adverse pregnancy outcomes: A nationwide study in Taiwan - Li-Ting Kao; Hui-Wen Yang; Yu-Tien Chang; I-Hsun Li; Liang-Hsuan Chen; Ya-Chiao Hu; Yi-Hsien Chen (Wolters Kluwer Medknow Publications, 2024)
Background It is unclear whether women with psoriasis who receive adequate management or achieve better control of their psoriasis before and during pregnancy could eliminate the negative effects. Objectives The objective of this study was to investigate the association between physician visits for psoriasis and adverse pregnancy outcomes. Methods This study used the National Health Insurance database and Birth Certificate Application in Taiwan. This research further categorized the study subjects into mothers with mild/severe psoriasis who visited physicians for psoriasis before delivery, mothers with mild/severe psoriasis who did not visit a physician for psoriasis before delivery, and mothers without psoriasis. Logistic regression was used to calculate the odds ratios (ORs) and 95% confidence intervals (CIs) for the occurrence of adverse pregnancy outcomes, including maternal and neonatal outcomes. Results 3,339 mothers with severe psoriasis, 41,296 mothers with mild psoriasis, and 2,017,271 mothers without psoriasis were included in this study. The mothers with mild/severe psoriasis demonstrated a significantly higher risk of labor complications and maternal risk factors. After adjusting for confounders, mothers with severe psoriasis who did not visit a physician for psoriasis demonstrated significantly higher odds of labor complications (OR 1.217), maternal risk factors (OR 1.507), having low-birth weight infants (OR 1.236), etc., than mothers without psoriasis. Conclusion This study demonstrated that mothers with psoriasis had a higher risk of adverse pregnancy outcomes. In addition, seeking medical care for psoriasis, particularly for women with severe psoriasis, appeared to exert a protective effect against adverse pregnancy outcomes.